Problem of Reinterpretation of the Achievements of the 16th Century French Historiography in the Work of Philippe Labbe (1607-1667) “A New Library of Manuscript Books» - E. V. Kuleshova; D. N. Starostin (Научный диалог)
Using the key historians of the so-called “French school” as an example, it is shown that the tendency of historical writing, laid down in the 16th century, underwent a critical reappraisal in the subsequent period. The authors of the article show that F. Labbe (1607-1667) in his work “The New Library of Manuscript Books” ( Nova Bibliotheca Manuscriptorum Librorum ) conceptually rethought the list of those historians who, in his opinion, deserve the attention of his contemporaries. It is alleged that works which subject matter was closely related to the interests of national monarchies appeared to be out of view. It is noted that F. Lubbe, as a representative of the Jesuit Order and, therefore, the spokesman for the interests of the Catholic Church, insisted on the need for cooperation between the papacy and the French kingdom. It is emphasized that, from the point of view of Labbe, the historical works of the 16th century deserved attention, which emphasized primarily the common historical fate of Western European states under the auspices of the church and the papacy as continuers of the Roman Empire’s tradition threatened by o the spread of the Reformation. The authors conclude that the reevaluation of the works of French historians of the 16th century by researchers of the next generation was far from always determined by a purely confessional point of view or proximity to royal power.